2014
DOI: 10.18544/pedm-20.02.0002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular disease in children with type 1 diabetes in 2000–2010 in Podlasie Province

Abstract: Contemporary patients frequently have excessive body weight and live in families burdened with risk factors for atherosclerosis. Despite the use of modern technology, metabolic control is not satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Low vitamin D levels can induce dyslipidemia, and lipid abnormalities, such as a rise in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels and a decrease in high-density lipoprotein cholesterol (HDL-C) levels, have been reported as significant risk factors for atherosclerosis and cardiovascular disease in adults [ 10 , 11 ]. The effects of serum vitamin D status on lipids in Chinese adults were investigated by Wang et al, who discovered that serum 25(OH)-D levels were closely related to lipids and AIP.…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin D levels can induce dyslipidemia, and lipid abnormalities, such as a rise in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels and a decrease in high-density lipoprotein cholesterol (HDL-C) levels, have been reported as significant risk factors for atherosclerosis and cardiovascular disease in adults [ 10 , 11 ]. The effects of serum vitamin D status on lipids in Chinese adults were investigated by Wang et al, who discovered that serum 25(OH)-D levels were closely related to lipids and AIP.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia frequency in diabetic children varies between 3.8% and 72.5% in different studies [14][15][16][17][18][19], and hypercholesterolemia was reported as the most frequent finding [16,[19][20][21]. Redondo et al found a dyslipidemia prevalence of 3.8% in the US with 11,348 T1D patients aged 2-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is associated with not only cardiovascular disease itself but also cardiovascular risk factors [8,9]. Low vitamin D levels could result in dyslipidemia, and lipid abnormalities—that is, an increase in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels and a decrease in high-density lipoprotein cholesterol (HDL-C) level—have been identified as important risk factors for atherosclerosis and cardiovascular disease in adulthood [10,11].…”
Section: Introductionmentioning
confidence: 99%